The Application of E-Module Based on Problem-Based Learning to Improve the Scientific Process Skill and to Reduce Misconceptionin the X MIA 2 Graders of SMA Batik 1 surakarta - Purnamawati, Henny; Karyanto, Puguh; Dwiastuti, Sri; Wulandari, Dynna Sri (Universitas Sebelas Maret, 2015)
This research aimed to reduce misconception and improve the scientific process skill in the X MIA 2 graders of SMA Batik 1 Surakarta through the application of E-Module based on Problem-Based Learning. This study was a Classroom Action Research consisting of 2 cycles. Each cycle consisted of four stages: planning, acting, observing, and reflecting. The subject of research was the X MIA 2 graders of SMA Batik 1 Surakarta consisting of 42 students. Techniques of collecting data used were multiple choice test and observation to measured scientific process skill, open-ended reasoning of Two-Tier Diagnostic Test to measure misconseption, and interveiw as the proponent data related learning process. The data were analyzed using descriptive qualitative technique consist of three component: data reduction, data presentation, and taking the conclusion. Data validation was carried out using triangulation method. Target of research was 20% to reduced misconseption and 30% to increased scientific process skill at the end of the cycle. The result of research showed that there was a decreased misconception in ecological concept: population of 51.31%, community of 43.73%, ecosystem of 39.36, and science, environment, technology and community (salingtemas) ecology of 54.33%. On the other side, theÂ result of research also showes that there was an increased scientific process skill in all aspects: observing of 36.52%, categorizing of 19.95%, predicting of 32.92%, interpreting of 33.75%, measuring of 35.66%, communicating of 38.31%, designing experiment of 48.80%, experimenting of 41.38%, asking question of 31.02%, hypothesizing of 31.62%, and applying concept of 39.38%. The conclusion of this research describes that the application of E-Module based on Problem-Based Learning is able to reduce misconception and improve the scientific process skill among the students.Â Keywords: E-Module based on Problem Based Learning, scientific process skill, misconception.